Sistem Informasi Geografis Untuk Menentukan Lokasi Pengembangan Pemukiman Menggunakan Metode Perbandingan Eksponensial - Lestari Handayani; Muhammad Fikry; Rendra Arga Swaperi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Pekanbaru is one of cities in Indonesia that is growing. Nit only physically evolved from the development side, the city of Pekanbaru also experiencing population growth. Population growth in the city of Pekanbaru will certainly pose new problems of residential land needs. The uneven distribution og the population in each district requires a solution to new settlements. To be able to determine the location of residential development designed a Geographic Information System (GIS). This system will calculate the feasibility of land to be used as residential areas by using the Comparative Method of Exponential (CME). Then this system will show the calculation results in the form of digital maps. This system has a feature to determine the public facilities of the nearby vacant land in each alternative location. This system uses administrative boundary map of Riau Province in 2005 and use the research data in 2005. In addition, this system can save the calculation results in a database, so it can be used without the need to run the function again CME. Keywords : Geographic Information System, population distribution, settlement